Taras Shevchenko’s Neologism Снігоквіт (Snihokvit): Psycholinguistic, Lexico-Semantic and Cultural Aspects - Vokalchuk, Halyna; Danylyuk, Nina; Lytvyn, Kateryna; Malevych, Lesya; Rohach, Oksana (East European Journal of Psycholinguistics, 2022)
The article focuses on the study of Taras Shevchenko’s linguistic identity through the free word association test results. The psycholinguistic experiment, “Author Neologisms of Taras Shevchenko,” held in 2019, involved four hundred forty-eight participants aged 14 to 61 y.o. Among them were professors, undergraduate and graduate students from Rivne State Humanitarian University, Lesya Ukrainka Volyn National University, Sarny Pedagogical College, National University of “Ostroh Academy”, Rivne Economic Technological College, National University of Water and Environmental Engineering, Borys Grinchenko Kyiv University, and M. Ocheret Zhytomyr City Humanitarian Gymnasium #23 (Ukraine). The responses of the recipients to the stimulus word снігоквіт/snihokvit (“snow blossom”), Shevchenko’s neologism, have been characterized based on grammatical (paradigmatic, syntagmatic, word-building), meaningful (thematic, reminiscent, reactions-personalities), and formal connections. The following semantic spheres to which the verbal responses belong have been defined: “Names of Flora”, “Natural Phenomena”, “Names of Actions”, “Colour Features”, “Haptic Features”, “Temporal Features”, “Abstract Notions”, as well as types of responses within the boundaries of associative fields. The specificity of a modern Ukrainian speaker’s perception of the meaning of a neologism taken out of the literary context has also been discovered. The authors have come to the conclusion that the poet created a highly artistic lexical neologism with the help of which he tried to communicate to the reader not only the primary meaning of the word лілея/lileya “white lily” (a flower) but also to provoke aesthetic feelings, and actualize the imagination about this special flower that is empowered with magic properties in the national linguistic map of the world. All the responses of the considered semantic spheres that belong to the associative fields of the author’s neologism снігоквіт/snihokvit give a better understanding of the lexicon of modern Ukrainian, the psycholinguistic peculiarities of the perception of Shevchenko’s figurative word. They also make it possible to trace specific changes in the conceptual map of the world and its perception. AcknowledgementsThe research was conducted within the complex scientific project, "Ukrainian Neology: Author Individual and Linguo-cultural Parameters" (state registration number 0117U005247), carried out by the Ukrainian Language Department at Rivne State Humanitarian University, Ukraine.